Parameters of ovarian reserve in relation to urinary concentrations of parabens - Joanna Jurewicz; Michał Radwan; Bartosz Wielgomas; Anetta Karwacka; Anna Klimowska; Paweł Kałużny; Paweł Radwan; Wojciech Hanke (BMC, 2020)
Abstract Background Parabens are synthetic chemicals commonly used in cosmetics, pharmaceuticals, food and beverage processing as antimicrobial preservatives. In experimental animals, parabens exposure was associated with adverse effects on female reproduction. Despite the widespread use of parabens little is known about their effect on female fecundity. The objective of the current analysis was to evaluate the associations of urinary parabens concentrations with parameters of ovarian reserve among women undergoing treatment in a fertility clinic. Methods Five hundred eleven female aged 25-39 years who attended the infertility clinic in central region of Poland for diagnostic purposes were recruited between September 2014 and February 2019. Urinary concentrations of parabens were measured by a validated gas chromatograohy ion-tap mass spectrometry method. Parameters of ovarian reserve were: antral follicle count (AFC), anti-Müllerian hormone (AMH), follicle-stimulating hormone (FSH) and estradiol (E2) levels. Results The geometric mean of specific gravity adjusted urinary concentrations of methyl (MP), ethyl (EP), propyl (PP), butyl (BP) and izobutyl paraben (iBuP) were 107.93 μg/L, 12.9 μg/L, 18.67 μg/L, 5.02 μg/L and 2.80 μg/L. Urinary concentrations of PP in the third quartile of exposure ((50-75] percentyl) were inversely associated with antral follicle count (p = 0.048), estradiol level (p = 0.03) and positively with FSH concentration (p = 0.026). MP, EP, BP and iBuP parabens were not associated any with parameters of ovarian reserve. Conclusions Chronic exposure to PP may potentially contributing to reduced fecundity and impair fertility. As this is one of the first study to investigate the potential effect of parabens on ovarian reserve further epidemiological studies with longer duration of observation are needed.